1994
DOI: 10.1063/1.467723
|View full text |Cite
|
Sign up to set email alerts
|

Is the depletion of ozone by HSO an exothermic process?

Abstract: The Oaussian-2 (02) theoretical procedure, based on ab initio molecular orbital theory, as well as other high level ab initio calculations [QCISD(T) and CCSD(T)/6-311 + +0(3df,2pd, and QCISD(T)/6-31I+0(5d2f,2p)] which avoid the additivity scheme of this theory, are used to estimate the heat of formation of HSO. For this purpose, we propose also, as a further improvement of the standard 02 scheme, to evaluate the residual correlation effects by using the QCISD(TQ) method, which is exact in fifth order rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…However, after the work of Xantheas and Dunning [10,11] with multireference methods and correlation consistent basis sets of up to quintuple-f quality, it seems well-established that HSO is more stable than SOH. Further theoretical investigations of Espinosa [12], Essefar [13], Wilson [14], Goumri [15], Decker [16], Denis et al [17,18] and Wilson et al [19,20] confirmed the preference of the HSO isomer.…”
Section: Introductionsupporting
confidence: 63%
“…However, after the work of Xantheas and Dunning [10,11] with multireference methods and correlation consistent basis sets of up to quintuple-f quality, it seems well-established that HSO is more stable than SOH. Further theoretical investigations of Espinosa [12], Essefar [13], Wilson [14], Goumri [15], Decker [16], Denis et al [17,18] and Wilson et al [19,20] confirmed the preference of the HSO isomer.…”
Section: Introductionsupporting
confidence: 63%
“…[43][44][45] The MG3S basis set fulfils this requirement. It is a basis set 46 identical to 6-3111G(2df) for C and O and to 311G(2p) for H. For the sulfur atom, this basis set stands for the 6-3111G(3d2f) Pople's one.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Because the reactions (1) and (3) are regarded as an ozone depletion cycle [4,5], a number of theoretical studies [6][7][8] of the HSO radical have been reported so far. In 1978 Schurath et al have observed theà 2 A 0 ÀX 2 A 00 system of HSO by chemiluminescence spectroscopy [9].…”
Section: Introductionmentioning
confidence: 99%